A Rare Chinese Family with Genetic and Clinical Expression of Danon Disease: Case Reports - Wang, Shuai; Cui, Yinghua; Pang, Shuchao; Wang, Qinglei; Zhai, Ning; Gan, Lijun; Yan, Bo (Cardiology and Cardiovascular Medicine, 2021)
Danon disease is a rare X-linked dominant disorder caused by the lysosome- associated membrane protein 2 (LAMP2) gene. It is characterized by the triad of hypertrophic cardiomyopathy (HCM), myopathy, and intellectual disability. Genetic analysis was performed to confirm LAMP2 gene mutation in a family with Danon disease. We collected the clinical data included electrocardiography (ECG), echocardiography, and cardiac magnetic resonance imaging (cMRI) in a family with Danon disease to reveal the clinical phenotype. Genetic analysis showed that LAMP2 gene deletion mutation (c.257_258delCC) in this family. The proband and his 13-year-old cousin developed HCM with a typical Wolff-Parkinson -White (WPW) pre-excitation pattern. cMRI with late gadolinium enhancement (LGE) further confirms the myocardial fibrosis. The clinical expression of Danon disease is different in different genders. Conclusions: Genetic and pharmaceutical approaches to upregulate LAMP2 gene expression may provide a novel therapy for patients with Danon disease.